Fadiga de aços TWIP de baixa densidade produzidos por conformação por spray e forjamento rotativo - Vidilli, André Luiz (2020)
The present study evaluated the mechanical properties in monotonic and cyclic stress of two low-density steel designed by thermodynamic calculations aiming stacking fault energy values that would allow different plasticity induced mechanisms to operate. The material was processed by spray forming, using recycled feedstock from mild steel and aluminum engine block. The deposit was mechanically formed by rotary swaging and subsequent annealing. This processing route resulted in single-phase austenitic materials with minimal texture. A high density of deformation twins (TWIP effect) was observed in the steel with lower aluminum content after the monotonic test, achieving a final elongation of 73%. The TWIP effect was also present in the alloy with a higher aluminum content, which deformed 56% before fracture. The fatigue limits were determined by the staircase method, and through microstructural characterization of the fatigued specimens, it was concluded that the mechanical twins are generated even in cyclic loading, influencing the fatigue crack nucleation and propagation stages.